Investor sentiment, limited arbitrage and the cash holding effect - Li, Xiafei; Luo, Di (Oxford University Press, 2017)
We examine the investor sentiment and limits-to-arbitrage explanations for the positive cross-sectional relation between cash holdings and future stock returns. Consistent with the investor sentiment hypothesis, we find that the cash holding effect is significant when sentiment is low, and it is insignificant when sentiment is high. In addition, the cash holding effect is strong among stocks with high transaction costs, high short selling costs, and large idiosyncratic volatility, indicating that arbitrage on the cash holding effect is costly and risky. In line with the limits-to-arbitrage hypothesis, high costs and risk prevent rational investors from exploiting the cash holding effect.